Nails as immune‐privileged sites: A case of disabling Acrodermatitis continua of Hallopeau successfully treated with Apremilast. Issue 4 (7th May 2019) - Lanna, Caterina; Cesaroni, Gaia Maria; Mazzilli, Sara; Lozzi, Flavia; Palumbo, Vincenzo; Diluvio, Laura; Bianchi, Luca; Campione, Elena
Abstract: Acrodermatitis continua of Hallopeau (ACH) is a chronic, inflammatory, and relapsing disorder characterized by the progressive destruction of fingernails and toenails. This condition is rare, difficult to treat, and often misdiagnosed. Several antipsoriatic treatments have been used, without any therapeutic guideline and no real improvement. Apremilast is an oral phosphodiesterase 4 inhibitor, approved for the treatment of chronic plaque psoriasis and psoriatic arthritis. It increases the intracellular concentration of cAMP and restores cytokine equilibrium, especially IL‐10, which is particularly involved in nail psoriasis. We reported the case of a 58‐year‐old man affected by ACH, successfully treated with Apremilast, who achieved a complete healing in just 1 month of treatment without any side effect. We suggest this drug as a successful new treatment for ACH, which can improve clinical manifestations rapidly and has no or few adverse effects. Future formal clinical trials and additional case reports are needed to establish the safety and efficacy of Apremilast in the treatment of ACH.